Urban Planning During Socialism Views from the Periphery - Mariotti, Jasna; Leetmaa, Kadri (Routledge Research in Historical Geography, 2024)
Urban Planning During Socialism delves into the evolution of cities during the period of state socialism of the 20th century, summarizing the urban and architectural studies that trace their transformations.　 The book focuses primarily on the periphery of the socialist world, both spatially and in terms of scholarly thinking.　The case study cities presented in this book draw on cultural and material studies to demonstrate diverse and novel concepts of 'periphery' through transformations of socialist cityscapes rather than homogenous views on cities during the period of state socialism of the 20th century. In doing so the book explores the transversalities of political, economic, and social phenomena; the places for everyday life in socialist cities; the role of professional communities on production and reproduction of space and ecological thinking. This book is aimed at scholarly readership, in particular scholars in architecture, urban planning, and human geography, as well as undergraduate, graduate, and post-graduate students in these disciplines studying the urban transformation of cities after World War II in socialist countries. It will also be of interest for planning officials, architects, policymakers and activists in former socialist countries.